Conducting trials on corticosteroid dosing for respiratory failure in the last paradise - Nobuaki Shime (Journal of Intensive Care, 2018)
Abstract It is interesting to find that Japanese clinicians continue to hesitate to change their practice even after accumulating evidence for the inefficacy of high-dose corticosteroid for ARDS in the Letters to the Editor discussion. Given the widespread use of the therapy even for other categories of acute hypoxemic respiratory failure with diffuse alveolar damage represented by acute exacerbation of interstitial pneumonia, Japan is the last part of the world in which efficacy of corticosteroid dosing (including pulse therapy) is assessed in those patients if they wish to continue this trend.